Nunca me esqueci de ti: a fotografia como memória de um lugar - Lino, Ana Isabel Barbosa (CEM – Cultura, Espaço & Memória, 2020)
Regarding the elaboration of this article, which results from an academic investigation in History of Photography, within the studies of Visual Culture, we selected a Portuguese photographic record, dating from the years 50/60 of the 20th century, whose thematic falls on the landscape of the area of Fontainhas (Porto). As the main goals, we intended to elaborate the analysis of the photograph, addressing technical and formal issues, as well as sketching a small study about the photographer, Jorge Henriques. Nevertheless, the image was mainly read from the point of view of the history of the place: one of the first public walks of the city, stage of festivities and memories.